2018
DOI: 10.1093/humrep/dey005
|View full text |Cite
|
Sign up to set email alerts
|

Perimenarchal air pollution exposure and menstrual disorders

Abstract: Shruthi Mahalingaiah: Reproductive Scientist Development Program HD000849, and a research grant from the Boston University Department of Obstetrics and Gynecology, Stacey Missmer: R01HD57210 from the National Institute of Child Health and Human Development and the Massachusetts Institute of Technology Center for Environmental Health Sciences Translational Pilot Project Program, R01CA50385 from the National Cancer Institute, Jaime Hart and Francine Laden: 5R01ES017017 from the National Institute for Environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Such pathway enrichment is in agreement with previous epidemiological studies, which confirmed that PM2.5 exposure is significantly associated with ovarian dysfunction, including menstrual disorders, lower reproductive capacity, and declined ovarian reserve. [ 50–52 ] Moreover, Cyp11a , Cyp19a , Cyp17a , and Hsd3b related to hormone synthesis were decreased significantly after exposure to PM2.5 for 4 months, while the expression of Hsd17b7 was markedly increased in PM2.5‐exposed ovaries. It has been reported that HSD17b7 mainly expresses in the corpus luteum, which may contribute to estradiol synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such pathway enrichment is in agreement with previous epidemiological studies, which confirmed that PM2.5 exposure is significantly associated with ovarian dysfunction, including menstrual disorders, lower reproductive capacity, and declined ovarian reserve. [ 50–52 ] Moreover, Cyp11a , Cyp19a , Cyp17a , and Hsd3b related to hormone synthesis were decreased significantly after exposure to PM2.5 for 4 months, while the expression of Hsd17b7 was markedly increased in PM2.5‐exposed ovaries. It has been reported that HSD17b7 mainly expresses in the corpus luteum, which may contribute to estradiol synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies have reported the association between airborne fine particulate matter exposure and menstrual disorders in women. [ 50,51 ] High concentrations of PM2.5 increases the risk of ovarian aging as evidence by significant decrease of antral follicle count, a sonographic marker of ovarian reserve. [ 52 ] Intrauterine exposure to diesel exhaust particles compromises the reproductive capacity of female mice and diminishes ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahalingaiah et al (12) and Carré et al (13) observed that all size fractions of particulate matter (PM) exposure and traffic-related air pollution are associated with incidence of infertility and adverse reproductive health (14). Merklinger-Gruchala et al (15) and Mahalingaiah et al (16) showed that the mean concentrations of the air pollutants particles 10 microns and below(PM 10 ), Sulfur dioxide(SO 2 ), Nitrogen Oxides (NO x ), and Carbon monoxide (CO) were associated with shortening of the luteal phase, an irregular menstrual cycle, menstrual disorders and menstrual irregularity, respectively. The above evidence suggested that although infertility and irregular menstrual cycle had many different anatomic or hormonal causes, they would be affected by air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to air pollution has been associated with several adverse reproductive and perinatal outcomes, including diminished semen quality and increased risks of menstrual irregularities, spontaneous abortion, hypertensive disorders of pregnancy, intrauterine growth restriction, preterm birth, and low birthweight . However, characterising a person's unique exposure to air pollution in studies of human health outcomes remains a challenging endeavour.…”
Section: Introductionmentioning
confidence: 99%